Is complete pathological response truly a complete response in breast cancer? - Rehman, Bushra; Sara Rehman; Sameen Mohtasham; Toqeer Zahid; Albash Sarwar; Muhammad Asad Parvaiz (Journal of the Pakistan Medical Association, 2023)
Objective: To check if complete pathological response in breast cancer is a good prognostic factor. Method: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data from January 2012 to December 2015 of all patients who received neo-adjuvant chemotherapy and had no distant metastasis at diagnosis. Mastectomy patients were excluded. Complete pathological response was defined as no detectable tumour cell in breast and axilla on pathological examination of the resected specimen. Tumour characteristics and 5-year disease free survival and overall survival were recorded. Data was analysed using SPSS 20. Results: Of the 353 patients whose data was evaluated, 91(25.8%) had complete pathological response. Mean age at diagnosis was 43+/-10 years. Among them, 62(68%) patients had grade III tumour, 39(42.9%) were negative for oestrogen receptor, 58(63.7%) were negative for progesterone receptor, 25(27.5%) were positive for human epidermal growth factor receptor 2, and 26(28.6%) patients were triple negative. Overall, 28((30.7%) patients had recurrence; 20(71.4%) had distant metastasis, 6(21.4%) had local recurrence, and 2(7.14%) had contralateral cancer. The 5-year disease-free survival and overall survival rates (Kaplan-Meier Survial curve) were 70% (28 patients-recurrence) and 87% (15 patients-deaths), respectively. Conclusion: Despite complete disappearance of tumour, a significant number of patients developed recurrences. Key Words: Complete pathological response, Neo-adjuvant chemotherapy, Survival, Metastasis.